The Impact of Financial Inclusion on Economic Growth based on East, West and Southern Africa - Fundji, Owandjokuna Jovial (International Journal of Economics and Financial Issues, 2024)
Financial inclusion plays a critical role in promoting economic growth. We conducted an empirical study to investigate the relationship between financial inclusion and economic growth in East, West, and Southern Africa. The study goes from 2009 to 2021, using a unique econometric method known as fully modified ordinary least squares. The results of the impact of financial inclusion on economic growth based on all countries, in all the models estimated, show that financial inclusion has statistically significant effects on economic growth. The research sample is separated into two groups according to the income. Financial inclusion has a positive impact on economic growth in high-income countries. Similarly, the study demonstrates that financial inclusion positively affects economic growth in low-income countries. Financial inclusion is a strategy that is now being utilized in sub-Saharan Africa to stimulate economic growth. National education policies should incorporate financial education, covering fundamental principles like savings, investment, risk, interest, credit, and banking. Policymakers should also educate students about the benefits of having a bank or mobile money account. To attract foreign investment, legislative proposals should improve the business climate, infrastructure, institutions, fiscal policies, rule of law, and corruption. Public authorities should collaborate with banks to establish favorable interest rates for rural investors.